2021
DOI: 10.1515/nanoph-2021-0192
|View full text |Cite
|
Sign up to set email alerts
|

Lab on optical fiber: surface nano-functionalization for real-time monitoring of VOC adsorption/desorption in metal-organic frameworks

Abstract: Metal-organic framework (MOF) nanomaterials are emerging porous coordinative polymers with large surface area and high porosity. Their application scenarios highly depend on adsorption/desorption dynamics of guest molecules in the framework. For representative ZIF-8 with framework flexibility, the study of molecule transportation in the pore channels of ZIF-8 will address the ambiguity of unclear application scenarios. In this study, the integration of lab-on-fiber technology and nanotechnology are demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…38–40 At the same time, real-time and remote sensing can be achieved with the benefit of advanced optical fiber sensing networks. 41…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38–40 At the same time, real-time and remote sensing can be achieved with the benefit of advanced optical fiber sensing networks. 41…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40] At the same time, real-time and remote sensing can be achieved with the benefit of advanced optical fiber sensing networks. 41 In optical fibers, the different modes of light are orthogonal and do not interfere with each other. A long-period fiber grating (LPFG) is a device with periodic refractive index change.…”
Section: Design and Simulation Of Lpfg Sensorsmentioning
confidence: 99%
“…With such, the exposure of guest vapours induced changes in the refractive index of the cladding that shifted the attenuation band. 162,[182][183][184] Hromadka et al have reported a LPG-based sensor working at phase-matching turning point presenting a high sensitivity for ethanol and acetone. 184,185 In another study, Chiang et al developed a fibre interferometer with pair of cascaded LPGs, where ZIF-8 was coated on the surface of the cladding.…”
Section: 34mentioning
confidence: 99%
“…LSPR is the collective oscillation of free electrons in metal nanoparticles/nanostructures irradiated by incident light at a specific frequency. It is widely applied in physical, 1,2 chemical 3,4 and biological 5–7 sensing due to sensitivity to the surrounding refractive index and enhancement of the localized electric field. Meanwhile, metal nanoparticle/nanostructure-based LSPR is more suitable for integration with miniaturized platforms (especially optical fibre tip (OFT)); therefore it is possible for achieving a plug-and-play remoting sensing probe which is used in harsh and restricted environments ( e.g.…”
Section: Introductionmentioning
confidence: 99%